2022
DOI: 10.1177/15330338221085357
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of CT-Guided Core Needle Biopsy in Pulmonary Ground-Glass and Solid Nodules Based on Propensity Score Matching Analysis

Abstract: Purpose: To compare the diagnostic accuracy and safety of computed tomography (CT)-guided core needle biopsy (CNB) between pulmonary ground-glass and solid nodules using propensity score matching (PSM) method and determine the relevant risk factors. Methods: This was a single-center retrospective cohort study using data from 665 patients who underwent CT-guided CNB of pulmonary nodules in our hospital between May 2019 and May 2021, including 39 ground-glass nodules (GGNs) and 626 solid nodules. We used a 1:4 P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 28 publications
0
11
0
1
Order By: Relevance
“…CTTB is routinely performed for diagnosis of pulmonary nodules. For GGN and PSN, diagnostic yield ranges from 80 to 100% [13, 14, 31‒33]. However, when compared to solid nodules, sensitivity for malignancy in SSN has been found to be relatively lower [14, 34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CTTB is routinely performed for diagnosis of pulmonary nodules. For GGN and PSN, diagnostic yield ranges from 80 to 100% [13, 14, 31‒33]. However, when compared to solid nodules, sensitivity for malignancy in SSN has been found to be relatively lower [14, 34].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study comparing ssRAB to CTTB for peripheral pulmonary nodules found a significantly lower risk of complications for ssRAB (4.4% vs. 17%; p = 0.002) [19]. Furthermore, in CTTB, mild hemorrhage has been described significantly higher when sampling GGN compared to solid nodules [14]. Potential for complications should be assessed when electing one procedure over the other, considering each individual patient’s risks.…”
Section: Discussionmentioning
confidence: 99%
“…Based on a single‐center study of 875 biopsies, Ruud et al 19 concluded that insertion through the interlobar fissure can cause clinically significant post‐biopsy pneumothorax and chest drainage. An et al 26 analyzed 665 lung biopsies based on propensity score matching analysis and concluded that biopsy puncture through the interlobar fissure was a risk factor for pneumothorax and recommended that biopsy should avoid traversing interlobar fissure as far as possible. Elshafee et al 27 found similar results in a retrospective analysis of 311 lung biopsies.…”
Section: Discussionmentioning
confidence: 99%
“…Computed tomography (CT) and ultrasound are the most widely used traditional imaging modalities for ablation guidance. It is widely acknowledged that CT-guided treatment of lung cancer via microwave ablation entails significant limitations, such as inaccurate ablation-needle puncturing and inaccurate assessment of the ablation boundary, which affect its therapeutic efficacy to a certain extent ( Lu et al, 2012 ; An et al, 2022 ). Magnetic resonance imaging (MRI) has limited value for diagnosing and treating lung diseases due to motion artifacts and low signals ( Boiselle et al, 2013 ; Ciet et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%